A representação temática da informação em TCC do Curso de Direito da UFPB: análise do vocabulário controlado no Repositório Eletrônico Institucional da UFPB. - Silva, Vânia Maria Ramos da (2013)
The current research analyzes the use of controlled vocabulary in information retrieval regarding the Course Conclusion Papers (TCC), of the Undergraduate Course in Law of the Federal University of Paraíba (UFPB), available at the Institutional Electronic Repository of UFPB (REI/UFPB). It highlights the institutional repositories available in digital environments as storage means of the university community scientific production as well as data dissemination and promotion of open access to scientific information. It deals with thematic representation of information and points out the use of controlled vocabulary as instrument for facilitating data retrieval. It aims at analyzing the contribution of the use of controlled vocabulary in data retrieval of REI/UFPB documents. The research approach is classified as qualitative. As to the development methodology, the elaboration of a controlled vocabulary in the Science of Laws area; the TCC indexing related to the Law course of UFPB/campus I, year 2011; the submission or insertion of the TCC in the UFPB Institutional Electronic Repository; and finally, data collection for analysis with the representatives of the researched sample, constituted by students from the undergraduate course in Law/campus I of the Federal University of Paraíba, were proposed. Data collection was characterized by the presentation of the REI/UFPB to the research participants and by the use of questionnaire. The result of research data analysis revealed that, from the users´ answers, the use of controlled vocabulary contributes to the information retrieval of the available TCC at the REI/UFPB. The students evaluated positively the controlled vocabulary and the Institutional Electronic Repository (REI) of the UFPB. On the other hand, they made up some suggestions for the improvement of this information retrieval system.